PERANCANGAN SISTEM INFORMASI PARKIR DENGAN QR- CODE BERBASIS WEBSITE PADA REAL ESTATE INDONESIA JAKARTA - zaetun Zaetun Zaetun (JURNAL REKAYASA INFORMASI, 2020)
ABSTRACT The current parking system is still manual, manual data processing certainly cannot keep up with the need for a fast, precise and accurate presentation of an information system. And manual data processing is considered ineffective for providing reports and information for companies that are developing having various transactions. With these various problems, the idea emerged to create a parking system with Qr- Code. Qr-code is the evolution of barcodes from 1 dimension to 2 dimensions developed by Denso Wave. Along with the development of information technology, security parking arrangement activities have also increased according to the complexity of the existing work, the existence of web technology that can be used as data processing, turns out to be quite interesting for several conditions to use it, one of which is in the problem of parking. Keywords : Parking System; QR-Code; Website